2016
DOI: 10.1080/00213624.2016.1249746
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Capital as the Source of Happiness: The Missing Economic Theory Underlying the Income-Happiness Paradox

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As a robust and general result, it has been found that richer people, on average, report higher subjective wellbeing. 14 The relationship between income and happiness, both in simple regressions and when a large number of other factors are controlled for in multiple regressions, proves to be statistically (normally highly) significant. In this sense, "income does buy happiness.…”
Section: Happiness and Difference In Income Between Personsmentioning
confidence: 99%
“…As a robust and general result, it has been found that richer people, on average, report higher subjective wellbeing. 14 The relationship between income and happiness, both in simple regressions and when a large number of other factors are controlled for in multiple regressions, proves to be statistically (normally highly) significant. In this sense, "income does buy happiness.…”
Section: Happiness and Difference In Income Between Personsmentioning
confidence: 99%
“…Fisher and Boulding suggest that "consumer capital" is the ultimate source of prosperity. The income-happiness relationship can be less relevant for economics as compared to the capital happiness relationship [141]. Social exclusion leads to less happiness, especially in the case of the people with mobility and disability issues, and consumers who purchase through online channels face more of unhappiness and less well-being [137].…”
Section: Physical Facilitiesmentioning
confidence: 99%
“…The influence of income on well-being is not constant but rather follows a logarithmic function [28]. This suggests that as income increases, the proportional gain in happiness decreases.…”
Section: Perspectives On Happiness Determinants In Microeconomicsmentioning
confidence: 99%